Basic researchThe immunohistochemical localization of secretory IgA in the submandibular gland of the Mongolian gerbil - Yuehuan, Liu; Xiwen, Chen; Jiusheng, Wu (Archives of Medical Science, 2008)
Introduction: Immunoglobulin A (IgA) plays an important role in local mucosal immunity. IgA-containing cells mainly occur in the duct system and the lumen of the glandular acini in the human submandibular gland. Material and methods: Immunohistochemistry technique was employed to survey the distribution of IgA in the submandibular gland of the Mongolian gerbil. Forty Mongolian gerbils consisting of 5 homozygous males and 5 homozygous females aged 21d, 90d, 360d and 720d were selected. Results: The gerbil submandibular gland can be discriminated into a secretory portion and a duct portion. The former mainly included serous acini and the latter contained intercalated ducts, striated ducts, granular convoluted tubules and interlobular ducts. IgA can be regularly visualized by 80°C heat isotope antibody retrieval (HIAR) after neutral formaldehyde fixation. The 1:100 HRP-conjugated goat anti-rat IgA is an effective antibody for evaluation of the IgA distribution in the gerbil. The results also demonstrated that the incubation time and temperature of primary antibody also influenced the staining results. IgA-positive cells were regularly presented in serous acini, intercalated ducts, striated ducts, granular convoluted ducts and interlobular ducts. They were also visualized in the connective tissues among the acini and ducts. The staining pattern appeared uneven among different secretory regions and duct regions. There were no regular changes according to the age. The positive reaction product was localized in the cytoplasm, while the nucleus was negative. Conclusions: IgA from local plasma cells or contributed from blood were transported into epithelial cells of acini and ducts by way of connective tissues underneath them.